Stepwise load reduction training: A new training concept for skeletal muscle and energy systems - Ozaki, H.; Abe, T.; Loenneke, J. P.; Katamoto, S. (Sports Medicine, 2020)
An increased ability to supply energy to skeletal muscle is expected to contribute to greater athletic performance, and therefore, a variety of training methods are used for improving these energy supply systems. These methods are classified into two broad categories: a bout of continuous exercise at a given load/intensity and intermittent bouts of exercise at a given load/intensity with recovery intervals. Interestingly, recent work suggests that a training method which starts at a high load/intensity and gradually decreases the exercise load/intensity within a given training set (stepwise load reduction training) may provide a range of adaptations. In resistance training, the load starts off high and is then reduced as the set continues which is expected to simultaneously increase muscle strength, endurance, and size. In training focused on aerobic and anaerobic metabolic systems, intensity starts off high and is then reduced as the exercise continues which is expected to simultaneously increase maximal anaerobic power, anaerobic capacity, and aerobic capacity. Because stepwise load reduction training has no recovery intervals between each load/intensity, the training effects are achieved within a short time per session (several minutes). However, only minimal evidence exists to support the effects of stepwise load reduction training; therefore, further studies with larger samples are needed.